Different forms of malnutrition among under five children in Bangladesh: a cross sectional study on prevalence and determinants. Issue 1 (December 2017) - Das, Sunanda; Gulshan, Jahida
Abstract Background This empirical study investigated the extent of malnutrition and factors associated with malnutrition amid children aged 0-59 months in Bangladesh using Bangladesh Demographic Health Survey data, 2014. Methods To examine the extent of malnutrition among the children under five in Bangladesh, we used Height-for-age, weight-for-height and weight-for-age. The association between the selected factors and nutritional status were assessed and logistic regression models were fitted for the three indicators. Results 36.2% children are stunted, 15% are wasted and 33% are underweight. Prevalence of stunting or underweight is lowest amongst children aged 0–6 months and highest at the age of 18 to 23 months (stunted 48% and underweight 37%). Wasting is highest in 0–6months. Odd of being stunted is 30% to 50% higher in Sylhet division as compared to other divisions. Other key covariates for stunting are urban area (OR = 1.226, p -value = 0.004), no or primary education of father (OR = 1.318, p -value < 0.001), no or primary education of mother (OR = 1.22, p -value = 0.002), underweight mothers (OR = 1.76, p -value <0.001) and wealth index poorest (OR = 2.892, p -value < 0.001). Important covariates for wasting are mother's occupation as physical labor (OR = 1.208, p -value = 0.018), underweight mothers (OR = 2.145, p -value <0.001) and wealth index poorest (OR = 2.892, p -value < 0.001). For underweight main covariates are: no or primary education of father (OR = 1.182, p -value = 0.011), no or primary education of mother (OR = 1.214, p -value = 0.002), mothers in physical labor (OR = 1.289, p -value < 0.001), underweight mothers (OR = 2.625, p -value < 0.001) and wealth index poorest (OR = 2.315, p -value < 0.001). Conclusions In addition to the ongoing programs to improve child health, government may wish to design targeted nutrition intervention strategies to make sure that health information and health education are easily accessible for parents. The most vulnerable groups including the children from poorest socio-economic group or children in the urban area require special attention. Mothers should also be given focus while designing intervention programs.